Entrepreneurship seminar learning experience and entrepreneurial intention change among Malaysian nascent entrepreneurs / Fauziah Pawan and Zainab Ahmad - Pawan, Fauizah; Ahmad, Zainab (Universiti Teknologi MARA, Perlis, 2011)
Drawing on the Theory of Planned Behavior, this study examines the effect of entrepreneurship seminar learning experience on entrepreneurial intention change of nascent entrepreneurs. This is necessary in order to gauge how participation and learning in short duration seminars may impact on nascent intentions to create a new venture- an important outcome for both the entrepreneur and policy makers. The study’s results show that entrepreneurial intention does change significantly in the course of the short duration seminar. The study also shows a positive learning experience and elevated levels of new knowledge and information among the seminar participants. In spite of this, the study’s results do not indicate that the learning experience has any significant impact on the intention change recorded. The findings contribute to the theories of planned behavior and entrepreneurial intention and have wider implications on the utilization of short duration seminars as a policy tool in nascent entrepreneur training and development.